2020
DOI: 10.1016/j.matt.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

A Green Selective Water-Etching Approach to MOF@Mesoporous SiO2 Yolk-Shell Nanoreactors with Enhanced Catalytic Stabilities

Abstract: To improve the stability of MOF catalysts, a design of MOF@mesoporous SiO 2 yolk-shell nanoreactors was developed via a mesoporous silica coating followed by selective water-etching strategy. Benefiting from their permeable mesoporous SiO 2 shells, exposed active sites on MOF surfaces, and protective shells, the yolkshell nanoreactors exhibit higher catalytic stability than bare MOF crystals in CO 2 cycloaddition, with product yield remaining unchanged upon three cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 50 publications
(68 reference statements)
0
42
0
Order By: Relevance
“…Such similar shelly mesoporous nature for SiO 2 has been also confirmed by recent works for CO 2 cycloaddition catalysis. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such similar shelly mesoporous nature for SiO 2 has been also confirmed by recent works for CO 2 cycloaddition catalysis. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…: ≈165.8 Wh kg −1 ) is superior to the ones reported in pioneering literatures, such as GeS 2 //Na 3 V 2 (PO 4 ) 2 O 2 F, SnS 2 @G//Na 3 V 2 (PO 4 ) 3 , Sb‐O‐G//Na 3 V 2 (PO 4 ) 3 , Sn 2 P 2 O 7 /RGO// Na 3 V 2 (PO 4 ) 3, MoSe 2 /N,P‐rGO//Na 3 V 2 (PO 4 ) 3 /C, Sb@TiO 2 //Na 3 V 2 (PO 4 ) 3 , or even much close to the level for advanced PNA//Na 1.5 VPO 4.8 F 0.7 . [ 18,38–48 ] Figure 6f displays the Max. specific capacity and energy when cells proceed after 200 times of cycling at respective current rates.…”
Section: Resultsmentioning
confidence: 99%
“…The MOF@mSiO 2 -YS has also been applied in catalytic cycloaddition of CO 2 to styrene oxide with tetrabutylammonium bromide as a cocatalyst. 4 It has been found that active species of this nanoreactor-like catalyst are only from Cr 3+ Lewis acid sites of MIL-101(Cr) nanocrystals and both catalytic activity and chemical stability of MIL-101(Cr) are improved owing to fully exposed active yolk surfaces and permeable mSiO 2 shell for the reactants and products. Furthermore, the protective role of the rigid mSiO 2 shell has also been elucidated because it could slow down the decomposition of MIL-101(Cr) nanocrystals encapsulated during the cycloaddition reactions.…”
Section: Mesoporous Silica Encapsulated Metal-organic Framework For Heterogeneous Catalysismentioning
confidence: 95%
“…3 In this issue of Matter, Yu et al have reported a new development of MOF@mSiO 2 yolk-shell nanostructure, in which MIL-101(Cr) nanocrystals serve as the yolk and mSiO 2 as the protecting shell. 4 The synthetic route they investigated is depicted in Scheme 1. Briefly, MIL-101(Cr) nanocrystals are first wrap-ped with a shell of mSiO 2 using silica source tetraethyl orthosilicate (TEOS) and colloidal template cetyltrimethylammonium bromide (CTAB).…”
Section: Mesoporous Silica Encapsulated Metal-organic Framework For Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation